2021
DOI: 10.1108/jedt-01-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of titanium alloy connecting rod based on structural topology optimization

Abstract: Purpose The purpose of this paper is to realize the lightweight of connecting rod and meet the requirements of low energy consumption and vibration. Based on the structural design of the original connecting rod, the finite element analysis was conducted to reduce the weight and increase the natural frequencies, so as to reduce materials consumption and improve the energy efficiency of internal combustion engine. Design/methodology/approach The finite element analysis, structural optimization design and topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Rezaei et al (2020) explored hydrogen production using renewable energy. Kulkarni et al (2018) reported reduction in greenhouse gas emission by using alternate material usage to reduce vehicle weight, while Zheng et al (2021) optimized connecting rod weight using alternate material, titanium. The weight reduction provided double folded advantages, less energy to operate and less amount of material used which, in turn, reduced energy consumption over product life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Rezaei et al (2020) explored hydrogen production using renewable energy. Kulkarni et al (2018) reported reduction in greenhouse gas emission by using alternate material usage to reduce vehicle weight, while Zheng et al (2021) optimized connecting rod weight using alternate material, titanium. The weight reduction provided double folded advantages, less energy to operate and less amount of material used which, in turn, reduced energy consumption over product life cycle.…”
Section: Introductionmentioning
confidence: 99%